(untitled) (Journal of Applied Business and Economics, 2022)
Moving goods and services is much easier than moving labor and obstacles to migration represent the biggest difference between the wave of globalization we are experiencing and that which occurred more than a hundred years ago. Universally, the General Agreement on Trade in Services (GATS) is the only multilateral treaty that specifically deals with the admission of migrants for labor purposes. Relevantly, according to some estimates, elimination of immigration controls would more than double the world’s real income. Despite the prospect of such significant welfare gains, migration is the most sensitive of all aspects of globalization, one of the most virulent political issues in international law and the unexplored frontier of globalization. Political realities largely explain the resistance, especially in wealthy countries, to liberalizing the flow of workers.